2009
DOI: 10.1063/1.3216585
|View full text |Cite
|
Sign up to set email alerts
|

Origin of photoactivity of oxygen-deficient TiO2 under visible light

Abstract: As it is now well established that oxygen vacancies are spontaneously introduced during nitrogen doping of anatase TiO2, there is a lively debate on whether nitrogen dopant or oxygen vacancy contributes to the visible light photoactivity of the doped catalyst. We showed that the coordinately unsaturated Ti site is integral to the visible light photoactivity in anatase oxygen-deficient TiO2 catalyst. Accordingly, oxygen vacancies may contribute to the visible light photoactivities in N-doped TiO2 and other nonm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
1
20
2
Order By: Relevance
“…Nevertheless, a nearly linear accumulation of H2 was achieved over all of the photocatalysts, indicating more stable photocatalytic performance. As compared to the pristine TiO2, TiO2−δ still demonstrated a higher activity, implying the importance of oxygen deficiency in this reaction [4,5]. Most importantly, CNT-TiO2−δ-15 and CNT-TiO2−δ-60 showed even higher H2 productivity than TiO2−δ.…”
Section: Figurementioning
confidence: 83%
See 2 more Smart Citations
“…Nevertheless, a nearly linear accumulation of H2 was achieved over all of the photocatalysts, indicating more stable photocatalytic performance. As compared to the pristine TiO2, TiO2−δ still demonstrated a higher activity, implying the importance of oxygen deficiency in this reaction [4,5]. Most importantly, CNT-TiO2−δ-15 and CNT-TiO2−δ-60 showed even higher H2 productivity than TiO2−δ.…”
Section: Figurementioning
confidence: 83%
“…One of the commonly observed and applied features for TiO2 is that its activity can be significantly enhanced by surface and/or bulk defects resulting from, for example, the introduction of heteroatoms or the removal of lattice oxygen [3,4,6]. Doping with metallic (Nb, Ag, Pt, W, Mn, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was reported that oxygen vacancies can enhance the visible light mediated catalytic activity to a very high level. 34 Therefore the enhanced photocatalytic reduction and oxidation activity of TiZr-6N-400 under visible light can be attributed to the synergistic effect of high surface area, oxygen vacancy and substantial N doping. So it is important to study the exact contribution of the oxygen vacancy as well as the non-metal doping separately for better understanding of the photocatalyst.…”
Section: Photocatalytic Performancementioning
confidence: 99%
“…More recently, it was observed that the same peak is observed in a titania material having oxygen vacancy. 34 Due to the creation of oxygen vacancies the adjacent oxygen atom experiences less electron density in comparison to other lattice oxygen atoms. Hence the peak due to these oxygen atoms shifts towards the higher binding energy.…”
mentioning
confidence: 99%